ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF BERAS SOLOK (Studi Kasus di Kota Solok ) (VIABEL: Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
The research on "Analysis of Comparative and Competitive Advantages of Solok Rice (Case Study in Solok City)" is aimed to analyze the competitiveness of Solok rice based on comparative and competitive advantages and looking at the impact of rice policy in Solok City.  The method used in this research is the case study method. The analytical tool used is the Policy Analysis Matrix (PAM). The results showed that rice farming in Solok City had comparative and competitive advantages, because a private profit of Rp. 6,454,307.44 and social benefits of Rp. 2,698,042,60. The results of the analysis obtained the value of PCR 0 and PC> 1. Farmer income will increase 31% if there is no market distortion carried out by the government because the SRP value obtained is 0.31.